AN ADVISORY COMMITTEE PROCESS TO PLAN MOOSE MANAGEMENT IN MINNESOTA - McGraw, Amanda M; Moen, Ron; Wilson, Grant; Edwards, Andrew; Peterson, Rolf; Cornicelli, Louis; Shrage, Mike; Frelich, Lee; Lenarz, Mark; Becker, Dennis (Lakehead University, 2010)
Concern over the decline of moose in Minnesota led to a Legislative Session Law mandating that the Department of Natural Resources (DNR) develop a Moose Management and Research Plan (MMP). Prior to developing the MMP, the DNR was required to form a Moose Advisory Committee (MAC). The MAC met 8 times in August 2008-July 2009 and provided management and research recommendations to the DNR in a 45-page report available on the internet. This paper details the MAC process and serves as a reference for agencies that find themselves in a similar management circumstance. Procedural decisions, planning needs, and development of the final report are discussed herein.